Desenvolvimento de uma DSL para a gerência de configuração de um sistema de gerenciamento integrado de redes - Pieroni, Rosangela (Universidade Federal de São Carlos, 2014)
The integrated network management system aims to manage the telecommunications network, regardless of network elements technology in order to identify the causes of problems, providing a more assertive decision making to remedy these problems and make the network available and operational. Thus, can to cater to the market that is increasingly demanding with the level of quality telecommunications products and services. Given this need, integrated networks management system belongs to a real company needs to respond quickly to customers' expectations with respect to requests for new functions system, and perform technology upgrades periodically. However, the integrated network management system development use centered-source technologies, and it requires great effort and hinders reuse. In this context, this master's project presents a proposal to facilitate the integrated network management system development using the techniques of MDD (Model Driven Development). MDD emphasizes the use of models in software development. These models specify the rules of business domain at a high level of abstraction, i.e., regardless of the programming language and to run the software platform. With appropriate computational tools transformations of models in the source code are performed. The use of MDD can provide software reuse procedurally, enabling faster development, lower cost, produce a flexible software and enable faster modifications. To apply MDD approach, a Domain Specific Language (DSL) for the configuration management of integrated network management system setting is designed to facilitate the inclusion of a new technology to be managed by the system, while providing faster development and with fewer errors of code. To evaluate the proposal, an experiment was conducted with the participation of software developers that know the system and work in this real company. The results showed that according to the descriptive analyses there was a reduction in the time spent in application development when it was used DSL compared to the specialization of classes. However, hypotheses tests showed no such reduction. The insertion of errors in the code occurred only in applications developed using specialization classes. The use of DSL provided a broader view of the business rule and you do not need knowledge of the programming language, once the code was automatically generated.
Keywords: Engenharia de software; Desenvolvimento orientado por modelos; Linguagem específica de domínio; Gerenciamento integrado de redes; Model driven development (MDD); Domain specific languages (DSL); Integrated network management; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO